Type Theory Comes of Age. - Wright, Alex (Communications of the ACM, 2010)
The article discusses the role of type theory in computer programming languages. Strongly-typed languages include javascript and Python, while C is a prominent example of a weakly-typed language. Statically-typed languages seek to detect errors when programs are compiled, whereas dynamically-typed ones perform their error detection at runtime. A goal of researchers has been to make static systems more flexible, and to this end various extensions have been introduced. Researchers have also been investigating the value of type systems in securing data privacy.